The Relationship between egg production and immune response in Breeders and their progeny Reared under Field Conditions - Al-Khadher, Ahmed (Yemeni Journal of Agriculture & Veterinary Sciences, 2021)
Immune system function is directly influenced by physiological status, as well as by many other factors. The objective of the current study was to evaluate the relationship between egg production and humoral antibody titers in breeder hens and further with the passive immunity of their egg yolk and progeny under Field Conditions. One vaccination schedule was followed for 15779 Ross-308 broiler breeders, divided into three replicates in 3 floor pens of the same farm through period of July 2010 to March 2011 . A total of 585 serum samples of the dame, 360 of hatched chicks and 360 egg yolk samples were obtained through the study period. Anti-Newcastle disease virus (NDV) and anti-infectious bursal disease (IBDV) antibody titers were evaluated using ELISA. The results revealed that there was a significant correlation (P<0.01) between egg production rates and mean of NDV anti body titers of hens’ sera, chicks sera and extracted egg yolk with a correlation coefficients of r = 0.42 , 0.55 and 0.76 respectively. Also correlation between egg production rates and mean of IBDV anti body titers of extracted egg yolk was significant (P<0.01) with correlation coefficients of r = 0.44, but no correlation was found with chicks sera (r=0.025) and was in negative direction with breeders’ sera (r= -0.33). The maternal antibody transferred to yolk and chicks’ sera were 81% and 83% in yolks, 73% and 81% in chicks and 91% and 97% from yolk to chicks for NDV and IBDV respectively. It has been concluded that, there is a significant correlation between egg production and humoral immune response in broiler breeders and antibody titers transmitted to their yolks and progeny under field conditions and recommended that more studies under field conditions with different vaccination schemes is require.